Negotiating birth: literacy and intercultural health communication in rural Indonesia - Subekti, Priyo; Sjuchro, Dian Wardiana; Fitriana, Rina; Tri, Nguyen Minh (Bricolage : Jurnal Magister Ilmu Komunikasi, 2026)
The impact of socio-cultural literacy and health communication on childbirth service preferences in rural Indramayu, Indonesia is investigated in this paper.  Even with national insurance programs providing better access to official medical treatments, many women still chose traditional birth attendants (TBAs) because of cultural comfort, trust, and local knowledge systems. The study consisted in 19 purposefully chosen informants: eight midwives, three TBAs, and eight moms who lately gave birth or were pregnant using a descriptive qualitative technique and a case study design.  Limited field observations and semi-structured interviews helped to gather data; Braun and Clarke's framework helped them to be thematically analyzed. The results expose seven main themes: (1) medical vs. traditional rationality in service preference; (2) fragmented and experience-based health literacy; (3) inclusive midwife-TBA partnerships enabled by local health centers; (4) symbolic rituals as informal health education; (5) structural barriers and access to healthcare; (6) interpersonal and culturally embedded communication channels; and (7) the collective role of family-particularly husbands and seniors-in decision-making.  According to the study, rather than only cognitive knowledge, cultural and social practices shape health literacy; moreover, communication strategies anchored in local symbols and trust are more successful than top-down messaging.  This study adds fresh understanding of community-based mother health systems combining indigenous knowledge with biomedical methods.The study has pragmatic ramifications for creating culturally sensitive health education plans that acknowledge the agency of modern and traditional health actors. It underlines the requirement of inclusive, culturally responsive communication to enhance rural mother health outcomes.